Preovulatory follicular dynamics, ovulatory response and embryo yield in Lacaune ewes subjected to synchronous estrus induction protocols and non-surgical embryo recovery - Figueira, Lucas Machado (2020)
The objective of this study was to assess the effect of the duration of progesterone-based estrus induction protocols on preovulatory follicular dynamics, ovulatory response, and embryo yield after non-surgical embryo recovery (NSER) in Lacaune ewes. Females received acetate medroxyprogesterone intravaginal sponges for six (G-6; n = 14) or nine (G-9; n = 14) days plus d-cloprostenol and eCG 24 h before sponge removal (Day 0). Preovulatory follicular dynamics and the luteal characteristics are evaluated by B-mode and Color-Doppler ultrasonography. NSER was performed five to six days after ovulation. The estrous behavior rate was 85.7% for both groups, and the percentage of ewes that ovulated was 92.9% in G-6 and 100% in G-9. The day of wave emergence (relative to Day 0) did not differ (P > 0.05) between G-6 (-3.0 +/- 0.5) and G-9 (-4.2 +/- 0.5). The number of follicles of size 4.1-5.0 mm was higher (P < 0.05) in G-9 (1.4 +/- 0.2) compared to G-6 (0.8 +/- 0.2) during the Days -4 to 0. At NSER, the transcervical penetration rate was 95.2% (20/21) and its duration time was lower (P < 0.05) in G-9 (3.4 +/- 0.6 min) than in G-6 (7.2 +/- 1.3 min). The number of ovulations and viable embryos was higher (P < 0.05) in G-9 (2.9 +/- 0.3 and 1.3 +/- 0.4, respectively) than in G-6 (1.9 +/- 03 and 0.4 +/- 0.2, respectively). In conclusion, the 9-day protocol promoted higher ovulation rate and embryo yield; moreover, the cervical dilation treatment allowed NSER in a high percentage of Lacaune ewes. (C) 2019 Elsevier Inc. All rights reserved.